1995
DOI: 10.3354/meps118283
|View full text |Cite
|
Sign up to set email alerts
|

A cross-system analysis of labile dissolved organic carbon

Abstract: The utilization of dissolved organic carbon (DOC) by bacteria in grazer-free cultures can be used to measure the concentration of labile DOC (DOCL). A database of 126 measurements was used to test whether or not the concentration of DOCL is positively related to total DOC. A positive and significant correlation between DOCL and DOC was found for the entire database as well as for lakes, rivers and seawater. An average response of about 0.17 pm01 DOCL pmol-' DOC could be calculated and 60% of the variance was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
195
5
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 296 publications
(233 citation statements)
references
References 63 publications
32
195
5
1
Order By: Relevance
“…Stepenauskas (1999) showed that bioavailability of DOM is enhanced after mixing of lake and ocean water. However, studying Cabiúnas lagoon (Northeast Brazil) that author showed that DOM of the ocean were more bioavailable than lake DOM, a result that corroborates previous cross-system comparisons (Søndergaard and Middelboe, 1995).…”
Section: The Functioning Process and Services Of Nclsupporting
confidence: 74%
“…Stepenauskas (1999) showed that bioavailability of DOM is enhanced after mixing of lake and ocean water. However, studying Cabiúnas lagoon (Northeast Brazil) that author showed that DOM of the ocean were more bioavailable than lake DOM, a result that corroborates previous cross-system comparisons (Søndergaard and Middelboe, 1995).…”
Section: The Functioning Process and Services Of Nclsupporting
confidence: 74%
“…To be incorporated into the microbial food web, large DOC molecules might be broken by sunlight into smaller and potentially more labile entities (Jørgensen et al, 1998;Wiegner and Seitzinger, 2001). About 17 % of the DOC was reported to be biologically available in lake, river, and marine ecosystems (Sondergaard and Middelboe, 1995). Recently, studies have shown that a significant fraction (∼ 30 %) of Arctic river DOC is degradable in the Arctic Ocean on a scale of 1-2 years (Alling et al, 2010;Holmes et al, 2008) -longer than the shallow shelf water residence time, which is on the order of several weeks (Nikiforov and Shpaikher, 1980;Semiletov et al, 2000).…”
Section: Biogeochemical Signatures Of Organic Matter Degradation In Smentioning
confidence: 99%
“…This fractionation between LDOC and SRDOC intends to represent the release of compounds of different labilities during cell lysis and sloppy feeding processes. The 10% attributed to the LDOC pool in the model is also close to the fraction of total DOC that is considered to be most labile (Sondergaard and Middelboe, 1995). We did not explicitly represent the labile fraction of DOP and DON in our model.…”
Section: Overviewmentioning
confidence: 99%